Implementasi Biaya Pencatatan Nikah Sebagai Tarif Penerimaan Negara Bukan Pajak di KUA Sulabesi Tengah - Akbar Takim (Sekolah Tinggi Agama Islam Babussalam Sula, 2024)
This study aims to analyze the implementation of Government Regulation No. 48/2014 on marriage registration tariffs at KUA Selabesi Tengah. The main problem encountered is the gap between the policy objectives and the reality of implementation in the field. The research method used was qualitative with a case study approach, involving in-depth interviews with KUA officials and wedding couples. The research findings show that although this policy aims to increase transparency, the community's preference to marry outside the KUA is still high due to cultural factors and social perceptions. Policy implementation faces challenges in socialization and adaptation to the local context. The contribution of this research is to provide an in-depth understanding of the dynamics of public policy implementation in a complex socio-cultural context and recommendations to improve the effectiveness of marriage policies in the regions. Keywords: Policy Implementation, Marriage Registration, KUA, Public Service